METAFORA DALAM MANTRA PENGOBATAN MASYARAKAT MELAYU KAYONG UTARA - Pratiwi, Nadya Cahya; Heryana, Nanang; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMetaphors in the Healing Mantra of North Kayong Malay Community. The research background was the curiosity of the researcher to discover the healing mantra from the North Kayong Malay community. .. This study aims to describe the metaphorical, function and methaphorical meaning in the north Kayong Malay healing mantra. . The research method used is descriptive qualitative. The data source was a Dukun in Siduk Village. Based on the findings of the metaphorical analysis, there were forms of the human, animate, living, object, terrestrial, substance, energy, and being. The metaphors of healing mantra from the North Kayong Malay community performed: (1) informational function, (2) expressive function, (3) directive function, (4) aesthetic function, and (5) phatic function. The meanings of healing mantra in the North Kayong Malay community: (1) connotative meaning, (2) stylistic meaning, (3) effective meaning, (4) reflexive meaning, (5) collocative meaning, and (6) thematic meaning. This research was expected to be teaching material references for teachers in school lessons. Keywords: Metaphor, Mantra, Healing.